Assessment of noise exposure for basketball sports referees. Issue 6 (2nd June 2016) - Masullo, Massimiliano; Lenzuni, Paolo; Maffei, Luigi; Nataletti, Pietro; Ciaburro, Giuseppe; Annesi, Diego; Moschetto, Antonio
ABSTRACT: Dosimetric measurements carried out on basketball referees have shown that whistles not only generate very high peak sound pressure levels, but also play a relevant role in determining the overall exposure to noise of the exposed subjects. Because of the peculiar geometry determined by the mutual positions of the whistle, the microphone, and the ear, experimental data cannot be directly compared with existing occupational noise exposure and/or action limits. In this article, an original methodology, which allows experimental results to be reliably compared with the aforementioned limits, is presented. The methodology is based on the use of two correction factors to compensate the effects of the position of the dosimeter microphone (fR ) and of the sound source (fS ). Correction factors were calculated by means of laboratory measurements for two models of whistles (Fox 40 Classic and Fox 40 Sonik) and for two head orientations (frontal and oblique).Results sho w that for peak sound pressure levels the values of fR and fS, are in the range −8.3 to −4.6 dB and −6.0 to −1.7 dB, respectively. If one considers the Sound Exposure Levels (SEL) of whistle events, the same correction factors are in the range of −8.9 to −5.3 dB and −5.4 to −1.5 dB, respectively. The application of these correction factors shows that the corrected weekly noise exposure level for referees is 80.6 dB(A), which is slightly in excess of the lower action limit of the 2003/10/EC directive, and a few dB below the Recommended Exposure Limit (REL) proposed by the National Institute for Occupational Safety and Health (NIOSH). The corrected largest peak sound pressure level is 134.7 dB(C) which is comparable to the lower action limit of the 2003/10/EC directive, but again substantially lower than the ceiling limit of 140 dB(A) set by NIOSH.